Drug'DNA Interaction Protocols - Fox, Keith R.; Fox, Keith R. (Methods in Molecular Biology,, 1997)
In Drug-DNA Interactions, expert researchers describe powerful molecular techniques designed to illuminate and explore the interaction of drugs and ligands with DNA, often perfected in their own laboratories, . These easily reproducible methods involve sequence recognition properties, as well as physical approaches to measuring both the strength of interaction and the mode of drug binding to DNA. Drug interactions are also examined from a cellular perspective and for their usefulness in the development of new therapeutic agents. Drug-DNA Interactions will be highly useful to all investigators needing the kind of detailed experimental and technical information often omitted from scientific papers. Those wishing to expand their repertoire of experimental techniques or to improve their current techniques will also find these powerful methods particularly helpful in elucidating the action of existing therapeutic agents, as well as in designing new anticancer drugs with improved action and reduced toxicity.